Estructura de la madera de Persea americana var. guatemalensis Mill (Hass) - Silva Guzmán, José Antonio; Fuentes Talavera, Francisco Javier; Richter, Hans G.; Angeles Alvarez, Guillermo; Sanjuan Dueñas, Rubén (Instituto de Ecología, A.C., 2016)
This paper presents the results of a study of the macroscopics and microscopic characteristics of the wood of Persea americana var. guatemalensis Mill ( Hass ). Samples were collected from commercial plantations.The study was motivated mainly by the situation prevailing around Mexican avocado production, and because this wood is considered to be underused. This study is part of a larger study on the technological characteristics of the wood of this species. From the fiber morphological relationships, an analysis is made about its characteristics as raw material for pulp and paper production. General information is included on the geographical distribution, taxonomy and reports on other studies and uses of this forest resource.